THE EFFECT OF THE MERIT SYSTEM AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE PADANG CLASS II A CORRECTIONAL FACILITY AND THE PADANG CLASS I CORRECTIONAL FACILITY - Faris Adhelflo; Naniek Pangestuti (Universitas Nusa Cendana, 2026)
This study aims to examine the influence of the merit system and work motivation on employee performance at the Class IIA Padang Correctional Institution and the Class I Padang Correctional Center. The background of this research is based on the importance of implementing competency-based and objective human resource management, as well as the increasing demands for improving the quality of public services. The study uses a quantitative approach with a survey method, where data were collected through questionnaires distributed to employees from both institutions. The collected data were analyzed using validity and reliability tests and multiple linear regression. The results of the study indicate that both the merit system and work motivation positively influence employee performance. Among the two variables, work motivation appears to be the more dominant factor in improving employee performance. These findings suggest that the implementation of a fair and transparent merit system, combined with efforts to strengthen employee motivation, can serve as an important foundation for enhancing performance within the correctional work environment. Keywords: Merit System; Work Motivation; Employee Performance; Socialization